Systematic Literatur Review (SLR): PowerPoint Interactive Learning Media in Elementary School - Isnaini Khalimatus Sa’diyah; Dwi Aqiella Fadilla Hayya; Taufiq Hanafi; Fina Fakhriyah; Erik Aditia Ismaya (Jurnal Prajaiswara, 2023)
Introduction/MainObjectives: The purpose of this research is to be able to find out and improve understanding of literature studies regarding PowerPoint interactive learning media in elementary schools using quantitative methods. Background Problems: The development of the era in the millennial generation, learning media has experienced a development. With the development of learning media able to provide creativity in the world of education. Interactive learning media is needed in learning, one of which is interactive learning media using PowerPoint in elementary schools. PowerPoint media really helps students in the learning process, because it has many features so that students like it more and are easy to understand. Research Methods: This type of research uses the Systematic Analyze Review (SLR) method. Data collection was carried out by reviewing articles regarding interactive PowerPoint learning media in elementary schools. Finding/ Results: Found 5 research articles from Publish or Perish, the data collection is obtained through Google Scholar from 2018 to 2023 with a limit of 200 articles according to predetermined keywords. Through identification, screening, eligibility, included, was eventually found 5 articles according to the specified keywords and restrictions. Conclusion: PowerPoint as this interactive learning media is very influential for students in the learning process and improve learning outcomes in elementary school.